2010
DOI: 10.1128/mbio.00084-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of an Expanded Inositol Transporter Repertoire in Cryptococcus neoformans Sexual Reproduction and Virulence

Abstract: Cryptococcus neoformans and Cryptococcus gattii are globally distributed human fungal pathogens and the leading causes of fungal meningitis. Recent studies reveal that myo-inositol is an important factor for fungal sexual reproduction. That C. neoformans can utilize myo-inositol as a sole carbon source and the existence of abundant inositol in the human central nervous system suggest that inositol is important for Cryptococcus development and virulence. In accord with this central importance of inositol, an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
89
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 73 publications
7
89
0
Order By: Relevance
“…Our previous functional studies on the seven group I ITR genes revealed that individual single mutations had no clear impact on fungal virulence and that this may be due to functional redundancy, but the ino1 itr1a double mutant did show virulence attenuation. This result suggests that inositol acquisition is important for the pathogenicity of C. neoformans (64).…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…Our previous functional studies on the seven group I ITR genes revealed that individual single mutations had no clear impact on fungal virulence and that this may be due to functional redundancy, but the ino1 itr1a double mutant did show virulence attenuation. This result suggests that inositol acquisition is important for the pathogenicity of C. neoformans (64).…”
mentioning
confidence: 56%
“…It is known that C. neoformans is one of a few yeast organisms that can utilize inositol as a sole carbon source (6,23). Recently, we identified inositol as one important compound for stimulating the sexual reproduction of this yeast (64,65). Furthermore, an unusually large ITR gene family has been identified in C. neoformans based on the sequence homology with known ITR genes in other organisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have shown that Cryptococcus contains an unusually large ITR gene family [15,16]. Based on our studies on two major ITR, Itr1a and Itr3c, we found that ITRs are required for full virulence of Cryptococcus, particularly during the fungal penetration of the BBB to cause infection of the CNS [9].…”
Section: Introductionmentioning
confidence: 99%